2011
DOI: 10.1007/s10875-011-9557-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Hizentra®, a New 20% Immunoglobulin Preparation for Subcutaneous Administration, in Pediatric Patients with Primary Immunodeficiency

Abstract: Subcutaneous IgG treatment for primary immunodeficiencies (PI) is particularly well suited for children because it does not require venous access and is mostly free of systemic adverse events (AEs). In a prospective, open-label, multicenter, single-arm, Phase III study, 18 children and five adolescents with PI were switched from previous intravenous (IVIG) or subcutaneous (SCIG) IgG treatment to receive dose-equivalent, weekly subcutaneous infusions of Hizentra® for 40 weeks. Mean IgG trough levels were mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 32 publications
14
49
0
Order By: Relevance
“…These findings suggest that the recognition of groups who may be at higher risk of lower pulmonary function may help to direct care and improve clinical outcomes in A-T. If Ig therapy is considered, most centres administer subcutaneous Ig, as is currently recommended for severe immundeficiencies [29][30][31].…”
Section: Immunoglobulin Replacementmentioning
confidence: 99%
“…These findings suggest that the recognition of groups who may be at higher risk of lower pulmonary function may help to direct care and improve clinical outcomes in A-T. If Ig therapy is considered, most centres administer subcutaneous Ig, as is currently recommended for severe immundeficiencies [29][30][31].…”
Section: Immunoglobulin Replacementmentioning
confidence: 99%
“…Historically, lifelong treatment of these types of PID with immunoglobulin (Ig) through various routes (e.g., intravenous (IV), subcutaneous (SC), intramuscular) has been wellestablished and has been shown to decrease the incidence of infections in these patients [1][2][3][4][5][6][7][8][9][10]. Moreover, SCIg therapy has been shown through several studies to be effective, safe, and well-tolerated in patients with PID [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. SCIg therapy may be beneficial for patients who are poor candidates for IVIg, have poor venous access, or have recurrent systemic infusion-related reactions (i.e., headache, fever, chills, or myalgia).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly with children, difficult venous access can be a barrier to IVIg therapy. The results from several studies have shown that SCIg in children is feasible and safe [14,16,19,[21][22][23][24][25]. It is now generally accepted that repeated SCIg infusions result in lower systemic adverse effects such as headaches and joint pain occurring within 72 h of the SC infusion [9].…”
Section: Introductionmentioning
confidence: 99%
“…In Poland, SCIG therapy was introduced in 2001 at the Children's Memorial Health Institute in Warsaw. Comparison of two methods in children revealed a slightly lower number of infections and days with antibiotics due to infections on subcutaneous infusions, indicating SCIG as a better choice of treatment in some group of patients [4,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%